Práticas de speaking no ensino remoto de língua inglesa: um estudo sob a perspectiva dos professores-bolsistas do projeto CEL - Sá, Beatriz Sousa de (Brasil, 2023)
Considering the interest of understanding how communicative activities can be practiced in remote teaching, since the social distance made physical interaction between teachers and students impossible during the pandemic of COVID-19, this work deals with speaking practices in the remote teaching of English, with the purpose of investigating how communicative activities were developed by the teacher-scholarship students of the CEL Project, from the Federal University of Amazon. For this purpose, it was also necessary to: a) describe the speaking practices developed and the technologies used; b) investigate the positive and negative results of the remote modality for these activities; and c) describe the teachers' beliefs about the efficiency of communicative practices in teaching English in the remote and face-to-face teaching. For the theoretical basis, books and scientific researches were used, such as Bygate (1987), Harmer (2010), Rao (2019), to address theoretical aspects of the speaking skills; and Santos, Beato, Aragão (2010), Warschauer and Healey (1998), Carvalho and Soares (2020), about the use of technologies in language teaching and oral skills, among other authors. This is a qualitative research with a case study technical procedure, where four teacher-scholarship of the CEL Project answered 5 subjective questions in an online form in the Google Forms platform. All the interviewees have experience in teaching English both face-to-face and remotely. The data collected was submitted to a descriptive-interpretative analysis. At the end of the study, a reflection is made about the integration of technologies in online teaching of speaking.